Comparing microbial populations from diverse hydrothermal features in Yellowstone National Park: hot springs and mud volcanoes - Rowe, Laura; Dowd, Scot E.; Davidson, Kelly; Kovarik, Claire; VanAken, Michayla; Jarabek, Alyssa; Taylor, Churro (Frontiers in Microbiology, 2024)
Geothermal features, such as hot springs and mud volcanoes, host diverse microbial life, including many extremophile organisms. The physicochemical parameters of the geothermal feature, such as temperature, pH, heavy metal concentration, etc. can influence the alpha and beta diversity of microbial life in these environments, as can spatiotemporal differences between sites and sampling. In this work, water and sediment samples were collected and analyzed from eight geothermal sites at Yellowstone National Park, including six hot springs, a mud volcano and an acidic lake within the same week in July 2019, and these geothermal sites varied greatly in their temperature, pH, and chemical composition. All samples were processed and analyzed with the same methodology and taxonomic profiles and alpha and beta diversity metrics determined with 16S rRNA sequencing. These microbial diversity results were then analyzed with respect to pH, temperature and chemical composition of the geothermal features. Results indicated that predominant microbial species varied greatly depending on the physicochemical composition of the geothermal site, with decreases in pH and increases in dissolved heavy metals in the water corresponding to decreases in alpha diversity, especially in the sediment samples. Likewise, sites with acidic pH values had more similar microbial populations (beta diversity) to one another than to relatively neutral or alkaline pH geothermal sites. This work suggests that pH and/or heavy metal concentration is a more important driver for microbial diversity and population profile than temperature for these sites and is also the first reported microbial diversity study for multiple geothermal sites in Yellowstone National Park, including the relatively new mud volcano Black Dragon's Caldron, which erupted in 1948.